PERFIL EPIDEMIOLÓGICO DE TENTATIVAS E ÓBITOS POR SUICÍDIO EM UM MUNICÍPIO DA REGIÃO SERRANA DO ESPÍRITO SANTO - Caliman, Maysa de Oliveira Silva (2020)
Introduction: Regarded as relevant public health problem in the world, the suicide issue has drawn attention to data quality in health management. As a surveillance strategy, the National Health System (SUS) uses Information Systems (SIS) to monitor harms